2003
DOI: 10.1001/archpedi.157.11.1115
|View full text |Cite
|
Sign up to set email alerts
|

Effective Pain Reduction for Multiple Immunization Injections in Young Infants

Abstract: Combining sucrose, oral tactile stimulation, and parental holding was associated with significantly reduced crying in infants receiving multiple immunization injections. Parents stated a strong preference for future use of this method, and nurses found the intervention injection technique easy to apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 29 publications
1
66
1
2
Order By: Relevance
“…51,52 Providers should address specific parental questions about the production and composition of the vaccines by directly providing the information requested. For example, for concerns about the presence of mercury (thimerosal) in vaccines, parents can be reassured that currently, none of the single-dose vaccine preparations given to infants contain any mercury.…”
Section: Figurementioning
confidence: 99%
“…51,52 Providers should address specific parental questions about the production and composition of the vaccines by directly providing the information requested. For example, for concerns about the presence of mercury (thimerosal) in vaccines, parents can be reassured that currently, none of the single-dose vaccine preparations given to infants contain any mercury.…”
Section: Figurementioning
confidence: 99%
“…Sucrose water (12%-50%; typically 1 packet of sugar in 10 mL of water) given immediately before an acute painful procedure has been shown to decrease pain in neonates and infants up to ϳ4 to 6 months of age. 57,73,74 Results from a systematic review of the literature support using sucrose to provide pain relief to infants undergoing venous access. 75 As for the mechanism, some have suggested that sucrose works via the activation of endogenous opioids, 76 although others have not found support for this hypothesis.…”
Section: Interventions For Young Infantsmentioning
confidence: 99%
“…The routine vaccine injections are some of the most common and most painful procedures during childhood especially when they are administered without adopting any pain management practice² , ³. Uncontrolled pain experience in early period of life has a negative and long lasting effect such as distress 4,5 and can negatively affect the development of central nervous system [6][7][8] . Moreover fear and avoidance of medical care during adulthood are partially related to experiences of many painful procedures and fears experienced during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Swaddling, holding, and providing the oral tactile stimulation of sucking on a pacifi er are effective non-pharmacologic approaches¹º -¹ 4 . Oral sucrose is an effective pharmacologic analgesic that acts via endogenous opioid pathways [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%